Parental risk attitudes and caries-related behaviours among immigrant and western native children in Oslo - Skeie MS, Riordan PJ, Klock KS, Espelid I. (Blackwell Synergy, 2006)
Immigrant children make up a large proportion of the school populations in many western cities.